2010
DOI: 10.1002/lt.22082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the middle hepatic artery and its relevance to living donor liver transplantation

Abstract: In comparison with the left and right hepatic arteries, there is a relative lack of information on the middle hepatic artery (MHA). In this study, data obtained by multidetector computed tomography from 145 patients were studied to evaluate anatomical variations of the MHA, a hilar artery that primarily supplies hepatic segment 4. An MHA was present in 103 (71%) of the subjects. In livers that had a replaced left hepatic artery, the MHA originated from the right hepatic artery; in livers that had a replaced ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 24 publications
5
35
2
Order By: Relevance
“…Previous studies showed contradictory results, which may be attributable to these differences in definition. Two recent studies indicated that the artery vascularizing S4 predominantly originated from the RHA and less frequently from the LHA, from both hepatic arteries or directly from the PHA in a trifurcation [8,12]. Our results are more in agreement with earlier studies [1,9,18], suggesting that the artery vascularizing S4 predominantly originates from the LHA and less frequently from the RHA, both hepatic arteries or the PHA.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies showed contradictory results, which may be attributable to these differences in definition. Two recent studies indicated that the artery vascularizing S4 predominantly originated from the RHA and less frequently from the LHA, from both hepatic arteries or directly from the PHA in a trifurcation [8,12]. Our results are more in agreement with earlier studies [1,9,18], suggesting that the artery vascularizing S4 predominantly originates from the LHA and less frequently from the RHA, both hepatic arteries or the PHA.…”
Section: Discussionsupporting
confidence: 91%
“…Studies that previously investigated the origin of this arterial branch, often used different definitions, and terms, such as A4 and MHA were interchangeably used [8,12,18]. From an anatomical point of view, the term MHA refers to a hilar artery that originates from the CHA or PHA, between the origins of the LHA and RHA, whereas A4 also can refer to a small intrahepatic branch that originates from the distal LHA or RHA [12]. Previous studies showed contradictory results, which may be attributable to these differences in definition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These rare types of variations are not seen in the present study. In a study of 145 subjects, Shaofa Wang et al [17] found middle hepatic artery ( MHA) in 103 (71%) of the subjects. [18] stated that middle hepatic artery (MHA) to the quadrate lobe came from RHA in 50% of cases, and in 44% of cases from LHA, and in 6% from the coeliac, hepatic artery, gastroduodenal artery and right gastric artery.…”
Section: Discussionmentioning
confidence: 99%